Exploring Globorotalia truncatulinoides coiling ratios as a proxy for subtropical gyre dynamics in the northwestern Atlantic Ocean during late Pleistocene Ice Ages. (14th May 2016) - Billups, K.; Hudson, C.; Kunz, H.; Rew, I.
Abstract: We explore the use of the coiling direction of planktic foraminifer Globorotalia truncatulinoides in sediment cores from the northwestern subtropical Atlantic Ocean as a proxy for variations in the intensity of the western boundary of the subtropical gyre over the past 280 kyr. Core‐top sediments from the study region are dominated by the left coiling variety consistent with the deep permanent thermocline at the study sites (KNR140‐37PC and Ocean Drilling Program Site 1059). Downcore G. truncatulinoides (sinistral) maxima occur in conjunction with 14 out of the 25 (Northern and Southern Hemisphere) precession maxima contained in the study interval. The agreement between the dominance of left coiling tests and the precession index of the Southern Hemisphere, in particular, supports a link between a deep thermocline in the northwestern subtropical Atlantic and northward flow of equatorially sourced warm surface currents, a situation analogous to the Late Holocene. Interglacial marine oxygen isotope stage (MIS) 5 lacks G. truncatulinoides (s) minima attesting to the relative stability of the western boundary during an interval of prolonged global warmth. G. truncatulinoides (s) disappear during the glacial extremes of MIS 2, 6, and 8 implying a weaker western boundary current at these times. Our results support that the coiling direction of this species is sensitive to variations in hydrography of the western boundary of the subtropical gyre. Because of the association between G. truncatulinoides (s) and precession maxima in both hemispheres, results support the importance of oceanic heat transport in half‐precession climate variability in the North Atlantic. Key Points: A 280 kyr record of Globorotalia truncatulinoides coiling ratios in the subtropical Atlantic Left coiling tests dominate during Northern and Southern Hemisphere precession maxima Coiling ratios track changes in the intensity of the western boundary current